SAT0539 Novel Bifunctional Inhibitors of Xanthine Oxidase and URAT1 Induce Profound Hypouricemia in Human Subjects. (10th June 2014) - Warrell, R.P.; Klukovits, A.; Barnes, K.; Satyanarayana, C.; Cheeseman, C.; Piwinski, J.
Abstract : Background: We have shown that a prototype anticancer drug (RLBN1001) induced marked hypouricemia in studies comprising >350 human subjects. Preliminary exploration suggested dual effects on uric acid (UA) production and excretion. Objectives: Given the unusual clinical potency, we sought to: (1) identify mechanism(s) of hypouricemia; (2) clarify structure-activity relationships (SARs) to targets of UA metabolism and genotoxicity; and (3) use these insights to develop analogs that would enhance the hypouricemic effects and eliminate genotoxic effects, thereby discovering potentially useful treatments for gout. Methods: Clinical proof-of-concept (POC) was verified by examining biochemical effects in 50 human subjects treated with RLBN1001. Recursive chemical syntheses were then conducted by exploring SARs using four principal bioassays: renal UA transporters URAT1 (SLC2A22) and splice variants of GLUT9a/b (SLC2A9); xanthine oxidase (XO); and in vitro mouse micronucleus (MMN) assays (to detect genotoxicity). Results: Over a 15-fold clinical dosing range with RLBN1001, nadir levels of hypouricemia (≤1.0 mg/dL) were not dose-related, indicating the minimal effective dose was below the lowest dose examined (100 mg/m 2 /d x 5d). At low and high doses, hypouricemia was associated with increased urinary excretion of both UA and total oxypurines. This drug was a potent inhibitor of URAT1 but not GLUT9a, a modest inhibitor of XO, and a potent clastogen in the MMN assay. We iteratively synthesized a library of novel analogs and identified new compounds that are potent inhibitors of both XO (i.e., 2-to-3 fold more potent than allopurinol) and URAT1 (5-to-45 fold more potent than lesinurad), but devoid of genotoxicity. One compound showed potent inhibition of GLUT9a, but other compounds showed minimal effects (data not shown). Data for reference and selected new compounds are shown in the table. Conclusions: Having established compelling clinical POC with the RLBN1001 prototype, we have synthesized a series of unique compounds with strongly enhanced activities that both reduce UA production and enhance UA excretion. A lead compound is expected to enter clinical trials as a novel, potential first-line treatment for hyperuricemic patients with gout. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2265